2020
DOI: 10.1177/0160017620957056
|View full text |Cite
|
Sign up to set email alerts
|

Inequality and Employment Resilience: An Analysis of Spanish Municipalities during the Great Recession

Abstract: In this paper we study an association almost neglected in the literature, that between income inequality and resilience. In particular, we explore the response of employment rates in the face of the crisis of 2008 and how income inequality levels may have affected this response. To do so, we construct two measures of employment resilience—resistance and recoverability—using data on total employment and self-employment for 995 Spanish municipalities during the Great Recession. Our results provide evidence of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 58 publications
(87 reference statements)
0
14
0
Order By: Relevance
“…Furthermore, inequality in cities has been associated with higher levels of crime, lower growth rates, political unrest and a decline in social cohesion (Glaeser et al (2009)). While Geelhoedt et al (2021) find that, in the case of Spain, high levels of inequality can negatively impact employment resilience in response to a shock from the larger macroeconomy.…”
Section: Discussionmentioning
confidence: 76%
“…Furthermore, inequality in cities has been associated with higher levels of crime, lower growth rates, political unrest and a decline in social cohesion (Glaeser et al (2009)). While Geelhoedt et al (2021) find that, in the case of Spain, high levels of inequality can negatively impact employment resilience in response to a shock from the larger macroeconomy.…”
Section: Discussionmentioning
confidence: 76%
“…Adaptive resilience highlights the changes that occur in a regional economy over time, as the system recovers from, adapts and reorients to a given shock (Holm and Østergaard 2015), allowing the emergence of new trajectories that emerge from the shock itself and local pre-conditions (Geelhoedt, Royuela, and Castells-Quintana 2021). In this sense, regional resilience is the ability of firms to adapt to change and shocks in competitive markets, technology, and policy environments shaping a region's evolutionary paths and dynamics (Simmie and Martin 2010).…”
Section: Regional Economic Resiliencementioning
confidence: 99%
“…Diversity creates a wide variety of knowledge, serving as a source of cross knowledge between sectors of the economy, thereby generating a wide range of opportunities for new economic activities (Grillitsch, Asheim, andTrippl 2018, Kahl andHundt 2015). In sum, more diversified regions can reduce the risk of possible shocks, as well as facilitate the generation of innovations and the emergence of new related trajectories (Balland, Rigby, and Boschma 2015b;Geelhoedt, Royuela, and Castells-Quintana 2021;Neffke and Henning 2013).…”
Section: Elements Of Cluster Resiliencementioning
confidence: 99%
See 1 more Smart Citation
“…Geelhoedt, Royuela, and Castells-Quintana (2021) study also employment resilience, in 995 Spanish municipalities during the Great Recession, with a specific focus on income inequality. They have a look at monthly data over the 2003–2018 period and study total employment and at self-employment, which is identified as a mechanism to escape unemployment and a gateway to entrepreneurial activity.…”
mentioning
confidence: 99%